Imbalance of essential and toxic elements in the biosamples of patients with surface gastritis with different secretory activity - Dikiy, N.P.; Layshko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Parhomenko, T.А.; Parhomenko, K.Yu. (Problems of Atomic Science and Technology, 2022)
The results of the application of various nuclear physics methods (characteristic X-ray radiation, gamma-activation analysis, and X-ray fluorescence analysis) to the study of the imbalance of certain elements in various biological samples (blood, hair, gastric mucus) in patients with superficial gastritis with increased and decreased secretory activity. The detection limit ranged from 10⁻⁴…10⁻⁷ mas.% of the mass. Particular attention was paid to sample preparation and the study of the analytical capabilities of the methods. It is shown that in this pathology there is an increased content of essential elements in the hair and a significant content of conditionally toxic and toxic elements in the blood and gastric mucus.